Flipped Classroom and Cooperative Work to promote High Order Thinking Skills - Alvarracín Alvarez, Aleida Monserrat (2022)
This article has a quantitative methodology and approach, a descriptive-correlational scope that collects students' perceptions about the application of the flipped and traditional classroom and presents the contribution of these two approaches to the development of higher thinking skills. This study took place in March, April, and May 2021. Two classes participated from a public high school in Quito, Ecuador, with students between 16 and 18 years old. The flipped classroom applied with 25 students; 29 students worked in the traditional classroom. Researchers collected information with a Likert questionnaire and another one with questions that measured higher cognitive abilities. The collected data received treatment with measures of central tendency and factorial analysis of multiple correspondences. Results reveal that the students of the inverted and traditional classrooms have positive perceptions regarding the two scenarios in which they worked. The results suggest slight advantages in analyzing and evaluating in the flipped classroom. In the final evaluation, students showed 5.5 points in the flipped classroom out of 10, statistically higher than the 4.7 average points observed in the traditional classroom. The data collected in the application of the flipped classroom are the strength of this study. Research that adds to the still scarce bibliographic sources about this subject during COVID 19 pandemic.